Ilmu Shorof dalam Perspektif Filsafat Ilmu : Sebuah Tinjauan - Moh. Zainal Abidin Aris; M. Yunus Abu Bakar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Ilmu Shorof, as an essential part of Arabic language studies, has a profound connection with the philosophy of science. This relationship encompasses aspects of study objects, methods, and goals that complement each other in understanding language. From the perspective of the philosophy of science, Ilmu Shorof is viewed as a structured knowledge system, a cultural product reflecting social values, and a tool for acquiring knowledge about the Arabic language, including religious and literary texts. Furthermore, Ilmu Shorof contributes philosophically to global language studies through its systematic approach. This research examines the relevance and philosophical implications of Ilmu Shorof in academic and practical contexts, offering a new perspective on the significance of this discipline in modern scholarship.